Governance, leadership, and compliance: Evidence on institutional ownership and executive characteristics from Indonesia - Kurnianto, Sigit; Khan, Muhammad Arsalan; Ilahiyah, Mar’a Elthaf (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2025)
Although corporate tax compliance has been widely studied, the role of institutional ownership in conjunction with executive characteristics remains underexplored. Most studies have focused on advanced economies, providing little understanding of how corporate governance frameworks can improve tax compliance in developing countries with evolving regulatory structures like Indonesia. This study addresses this gap by examining the effect of institutional ownership on tax compliance among non-financial firms listed on the Indonesia Stock Exchange from 2020 to 2024, with executive character as a moderating factor. Using 1,268 firm-year observations, the analysis employs descriptive statistics, Pearson correlations, and multiple linear regression. The findings indicate that institutional ownership positively affects tax compliance, thus supporting the agency theory perspective that institutional investors mitigate tax compliance gaps and enhance overall governance. These findings imply that institutional ownership improves tax compliance through enhanced governance and curtailing aggressive tax avoidance. When executives are risk-averse, the governance benefits are enhanced, but the effect is diminished when executives are risk-taking. High profitability and larger firm size bolster compliance capability, while high leverage places firms under pressure toward non-compliance.